2017
DOI: 10.1097/rli.0000000000000339
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Renal Failure Accentuates T1 Signal Enhancement in the Deep Cerebellar Nuclei of Gadodiamide-Treated Rats

Abstract: ObjectivesThe purpose of this preclinical study was to investigate whether moderate chronic kidney disease is a factor in potentiating gadolinium (Gd) uptake in the brain.Materials and MethodsA comparative study was performed on renally impaired (subtotal nephrectomy) rats versus rats with normal renal function. The animals received 4 daily injections of 0.6 mmol Gd/kg a week for 5 weeks (cumulative dose of 12 mmol Gd/kg) of gadodiamide or saline solution. The MR signal enhancement in the deep cerebellar nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 43 publications
9
52
0
Order By: Relevance
“…It is clear from the evaluation of animals receiving such agents that renal dysfunction (with the correlate in patients being mild or moderate chronic kidney disease) potentiates deposition of gadolinium not only in the cerebellum but also in the brain and bones. 61 These results are fully consistent with a prior clinical study, 62 thus stressing the translational value of most nonclinical studies.…”
Section: Additional Issuessupporting
confidence: 83%
“…It is clear from the evaluation of animals receiving such agents that renal dysfunction (with the correlate in patients being mild or moderate chronic kidney disease) potentiates deposition of gadolinium not only in the cerebellum but also in the brain and bones. 61 These results are fully consistent with a prior clinical study, 62 thus stressing the translational value of most nonclinical studies.…”
Section: Additional Issuessupporting
confidence: 83%
“…In renally impaired rats, when compared with rats with normal renal function, gadolinium uptake, after multiple injections of gadodiamide, was potentiated in the cerebellum, brain, and bones. 34 This study also showed that plasma gadolinium was predominately in a disassociated, soluble form. Total Gd concentration in the brain correlated with renal function.…”
Section: Recent Animal Investigationsmentioning
confidence: 61%
“…46 Evidence-from both clinical and preclinical studies-to date favors that patients with impaired renal function are at higher risk for gadolinium accumulation in the brain and in bone, with this conclusion applying only to the group of agents that have such gadolinium deposition, the linear chelates. 34 Both cited studies furthermore noted deposition of gadolinium in the choroid plexus (beyond what was previously established, specifically the dentate nucleus and the globus pallidus). The Cornell and Columbia groups subsequently published a study of patients receiving 35 or more linear GBCA administrations with normal renal function.…”
Section: Minimizing Riskmentioning
confidence: 99%
“…One reason for using contrast material, nonetheless, is improved image quality. We have shown that ferumoxtyol significantly improves aortic annulus image quality compared with unenhanced MR angiography, resulting in better measurement reproducibility (3). A second possible reason is imaging time reduction.…”
Section: Disclosures Of Conflicts Ofmentioning
confidence: 95%